PEMBERDAYAAN SRIKANDI ASI SEBAGAI DUTA PROMOSI ASI DI WILAYAH KECAMATAN NGAMPILAN - Rahmah -; Erfin Firmawati (LPPM IST AKPRIND Yogyakarta, 2018)
Nationally, the coverage of exclusive breastfeeding in Indonesia in infants 0-6 months fell from 28.6% in 2007 to 24.3% in 2008, and increased again to 34.3% in 2009, related to that in the program the healthy improvement of healthy nutrition in 2010 is set by the national target of exclusive breastfeeding achievement is 80%, but in fact the coverage of exclusive breastfeeding in Indonesia in 2010 has not reached the target. Coverment of exclusive breastfeeding is influenced by several factors, especially the very limited energy of breastfeeding counselors, legislation on breastfeeding, lack of education, socialization, advocacy, and campaigns related to breastfeeding and breastfeeding, lack of facilities and infrastructure, as well as non-optimal support of breastfeeding support groups (Depkes RI, 2009). The issue of exclusive breastfeeding is a major and shared issue that concerns the State, the city government of Yogyakarta in particular and the Muhammadiyah-Aisyiah organization, as it is in line with the Quranic injunction Qs.Al Baqarah: 233 for mothers to breast-feed their children this joint concern can be realized by forming a support group of ASI in the community with optimization of posyandu cadres. Besides the training, this activity is also accompanied by assistance to the posyandu cadres so that they can be as Srikandi ASI/promoter of breast milk in the community.